100 first words - Sirett, Dawn; Milner, Charlotte (London Dorling Kindersley Limited, 2017)
Labeled pictures introduce the words for clothes, colours, toys, animals, and food
Linguistic Notions
1 2 23
Keywords: Board books; Vocabulary -- Juvenile fiction